bỏ số 1 ở đầu thì giải dc á, còn có số 1 thì chịu
\(\dfrac{1}{x+2x}+\dfrac{1}{x^2+6x+8}+\dfrac{1}{x^2+10x+24}+\dfrac{1}{x^2+14x+48}=\dfrac{4}{105}\)
\(\dfrac{1}{x\left(x+2\right)}+\dfrac{1}{\left(x+2\right)\left(x+4\right)}+\dfrac{1}{\left(x+4\right)\left(x+6\right)}+\dfrac{1}{\left(x+6\right)\left(x+8\right)}=\dfrac{4}{105}\)
\(\dfrac{2}{x\left(x+2\right)}+\dfrac{2}{\left(x+2\right)\left(x+4\right)}+\dfrac{2}{\left(x+4\right)\left(x+6\right)}+\dfrac{2}{\left(x+6\right)\left(x+8\right)}=\dfrac{8}{105}\)
\(\dfrac{1}{x}-\dfrac{1}{x+2}+\dfrac{1}{x+2}-\dfrac{1}{x+4}+\dfrac{1}{x+4}-\dfrac{1}{x+6}+\dfrac{1}{x+6}-\dfrac{1}{x+8}=\dfrac{8}{105}\)
\(\dfrac{1}{x}-\dfrac{1}{x+8}=\dfrac{8}{105}\)
\(\dfrac{x+8-x}{x\left(x+8\right)}=\dfrac{8}{105}\)
\(\dfrac{8}{x.\left(x+8\right)}=\dfrac{8}{105}\)
\(\Rightarrow x\left(x+8\right)=105\)
\(x^2+8x-105=0\)
\(\left(x-7\right)\left(x+15\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=7\\x=-15\end{matrix}\right.\)
không có số 1 ở đầu đâu.Mong mọi người giải giúp mk nhé!